Silenced Narratives, Enduring Wounds: A Feminist Examination of Trauma and Power in Anuradha Roy's Sleeping on Jupiter - Rahim, Asma; Khan, Abdul Hamid (Pakistan Languages and Humanities Review, 2024)
This research paper examines the portrayal of women’s trauma and its frequent misinterpretation within the androcentric society, as depicted in Anuradha Roy’s novel, Sleeping on Jupiter. Through a feminist analysis of the novel, the study analyzes how societal norms not only shape the experience of trauma but also its recognition and authentication. The research is qualitative in nature and explores the concept of “insidious trauma,” and “secret trauma,” faced by the protagonist in the given novel which is often ignored due to the biased nature of the social and cultural norms. The research follows Cathy Caruth's concept of trauma as a methodological framework. The research concludes that the seemingly ordinary experiences, silenced narratives, and gender disparities significantly contribute to the inadequate representation of women’s trauma. This novel el can further be explored from the perspective of intersectionality to examine how race and d gender identity impact the experiences of abuse survivors.